Comparative Study of Learning Outcomes among Students Engaged in Student Organizations and Those Not Participating in Student Organizations - Moh. Hafid (PT Mattawang Mediatama Solution, 2024)
This research aims to compare the learning outcomes of students who actively participate in student organizations with students who do not participate in student organizations in Basic Mathematics courses. The research design utilized a quantitative comparative approach with two sample groups, each consisting of 34 students who actively participate in organizations and 33 students who do not participate in organizations. The research instrument was a basic mathematics learning outcomes test, including objective and subjective aspects. The results of statistical tests indicated that the average score of students who actively participate in organizations (77.21) is higher than students who do not participate in organizations (72.58). Data analysis using the t-test showed a significant difference between the both groups (p = 0.026), confirming that students who are active in student organizations have better academic achievements. These findings support the alternative hypothesis, which states that there are significant differences in learning outcomes between the two groups. These results have the implication that participation in student organizations can make a positive contribution to student learning outcomes. Therefore, it is recommended for educational institutions and students to consider the potential benefits of involvement in student organizations as a strategy to improve academic achievement.